Moeed Yusuf (Ed.), Pakistan’s Counter Terrorism Challenge - Syed Sadam Hussain Shah (CISS Insight Journal, 2018)
In the introductory chapter Moeed Yusuf argues that the Taliban’s activities in Afghanistan and Islamic radical movements elsewhere impact the morale and resource availability to militant groups in Pakistan. However, this assertion is not universally true. For example, if an Afghan Shia militia is gaining strength and popular support it will not favour Tehrik e Taliban Pakistan or a Takfiri militant outfit. The domino effect primarily depends on factors such as common ideology and strategic ambitions. This chapter does not discuss the important factors, which impact the non-state actors’ activities in the state. In chapter 1 Moeed Yusuf mainly argues that Pakistan’s civilian and military authorities remain in a race against time to pacify Islamist militancy engaged in generating violent opposition to the state. The state is unlikely to succeed unless the military expands its operational capacity and the government addresses many institutional weaknesses that constrain a coherent anti-terrorism policy and Pakistan’s regional security environment. However, Pakistan has overcome many of the difficulties in implementing its anti-terrorist policies since the book was published.